Diastereoselective trans Cyclopropanation of 3-Alkylidene Oxindoles with In Situ Generated α-Diazo Carbonyls or α,β-Unsaturated Diazo Compounds - Pramanik, Sayan; Ray, Suman; Maity, Suvendu; Ghosh, Prasanta; Mukhopadhyay, Chhanda (Synthesis, 2021)
An efficient diastereoselective trans cyclopropanation of 3-alkylidene oxindoles with in situ generated α-diazo carbonyl compounds or α,β-unsaturated diazo compounds under metal-free conditions has been developed to synthesize 3-spirocyclopropyl-2-oxindole derivatives. The procedure is based on the 1,3-dipolar character of the corresponding diazo compounds under base-catalyzed conditions. The method has a wide substrate scope and uses easily available starting materials.
Keywords: diastereoselectivity; trans cyclopropanation; diazo compounds; 1,3-dipoles; spiro compounds; oxindoles